Studi Literatur : Tentang Penggunaan Aplikasi Quizizz terhadap Keaktifan, Minat, Motivasi dan Hasil Belajar pada Mata Pelajaran IPS Siswa Kelas Tinggi Sekolah Dasar Di Indonesia Tahun 2020-2024 - Rosita, Vera Galuh; Dhiniaty Gularso (JKPD (Jurnal Kajian Pendidikan Dasar), 2024)
This study aims to analyze the effect of the quizizz application on activeness, interest, motivation, and learning outcomes in social studies subjects for high school students. This research was conducted using the literature study research method. Data sources in the form of journals used in this research were obtained and collected through digital platforms with the  publish or perish 8 application, Google Scholar, Garuda, and Sinta. The analysis technique used is literature review with the stages of collecting secondary data sources, criticizing sources both external and internal, interpreting or analyzing data, and historiography or writing research results, and the final step is drawing conclusions based on data analysis and research results. The results of the study concluded that the quizizz application has an effect on student activeness, interest, motivation, and learning  outcomes, as evidenced by 24 journals stating that quizizz has a positive influence on increasing activeness, interest, motivation, and learning outcomes. Of the 24 journals that have been analyzed, it can be seen that the percentage of improving students' learning abilities with the help of the quizizz application is 100%, which means that all of these journals have the same opinion that quizizz has a positive influence on improving students' learning abilities. The improvement of students' learning abilities in 4 groups, including: (1) there are 21% of journals stating that quizizz has an influence on increasing social studies learning activeness, (2) there are 11% of journals stating that quizizz has an influence on increasing social studies learning interest, (3) there are 14% of journals indicating that quizizz has an influence on increasing social studies learning motivation, and (4) there are 54% of journals agreeing that quizizz has an influence on increasing social studies learning outcomes.